PERLINDUNGAN HUKUM UNDANG-UNDANG NOMOR 30 TAHUN 2014 BAGI PEGAWAI NEGERI SIPIL YANG DIBERHENTIKAN DAN IMPLIKASINYA TERHADAP KEWENANGAN BADAN PERTIMBANGAN KEPEGAWAIAN - Arief Rachman Hakim (MIH Unsoed, 2018)
Legal protection of civil servants (PNS) in a dispute over staffing has undergone a paradigm shift with the enactment of Law No. 30 of 2014 on Government Administration (UUAP). The paradigm change then has implications for the authority of the Civil Service Advisory Board (BAPEK). This study aims to analyze how UUAP provide legal protection to the Civil Servant who was dismissed not because of disciplinary punishment of civil servants and what are the implications of the legal protection against BAPEK authority.This research is normative legal research with qualitative analysis through conceptual approach and legal approach to legal issue which become subject matter in research. Conclusions are drawn deductively through a coherent and systematic description. To support this research, the authors conducted interviews with some of the top officials at BAPEK in Jakarta as complementary data supporting the research analysis.Based on the results of the study, the enactment of the UUAP which has established the regulation of administrative efforts in Articles 75 to 78, carries the legal consequence that the dismissed civil servant which not due to disciplinary punishment may undertake dispute resolution through administrative measures even though the relevant rules governing it, do not provide a dispute resolution through Administrative effort. This then implies the widespread authority of BAPEK, which before the enactment of UUAP is only authorized to handle administrative appeals of personnel disputes caused by the dismissal of civil servants due to disciplinary punishment.